دراسة مهارات القراءة لدى التلاميذ المتأخرين لغويا دراسة ميدانية لخمس حالات بمدينة الأغواط - لغريبي صفاء; صفراني فاطمة الزهراء; بن عابد جميلة (My University, 2022)
The current study aimed to study the reading skills of a group of primary school students who suffer from language delays. The sample consisted of five schoolchildren in the third and fourth grades of primary school, who were deliberately chosen from the original community that represents two primary schools in Laghouat. The descriptive approach was applied with Using the research tools that were represented in the Oral Comprehension Test (ELO) Abdelhamid Khomsi, which was adapted by Adda Dalila to the Algerian environment in 2016, and the reading test L’alouette by the researcher Lefavre, where 6102 which was adapted by Fatiha bin Saadoun on the Arab environment information and data were collected and processed statistically, and The study resulted in the following result : .The linguistically delayed student suffers from a decline in the level of reading skills. Accordingly, we came through the current study to verify the hypothese of our research, which confirms that the linguistic delay has a significant impact on reading skills, as it is related to the oral and written aspects of the language